High-throughput drug screening to investigate blood-brain barrier permeability in vitro with a focus on breast cancer chemotherapeutic agents - Curtaz, Carolin J.; Wucherpfennig, Sophia; Al-Masnaea, Emad; Herbert, Saskia-Laureen; Wöckel, Achim; Meybohm, Patrick; Burek, Malgorzata (Frontiers in Drug Delivery, 2024)
Therapy of cerebral diseases such as brain metastatic breast cancer is still challenging. Due to the blood-brain barrier (BBB), a tight barrier that protects the brain and prevents the passage of many drugs, therapeutically sufficient drug concentrations in the brain are often not achieved. Therefore, methods and drugs to manipulate the BBB permeability are required. Here we used high-throughput screening (HTS) to identify chemicals that may increase BBB permeability. Human BBB in vitro model derived from hematopoietic CD34 + stem cells (differentiated to brain-like endothelial cells, BLECs) was used. BLECs were seeded on 96-well plates coated with biotinylated gelatin, treated with respective chemicals for 24 hours followed by addition of FITC-avidin for permeability estimation. Selected substances were further tested in vitro on BLECs. Cell viability, gene and protein expression were measured using CellTiter-Glo ® , qPCR and Western blot, respectively. From 1278 compounds, we identified 175 substances that cause at least a 50 percent increase in BBB permeability. Two substances from the substance classes used in breast cancer therapy, GW2974 (tyrosine kinase inhibitor) and 4-amino-1,8-naphthalimide (ANI) (PARP inhibitor), were analyzed in more detail. ANI was nontoxic to BLECs, while GW2974 decreased or increased viability depending on the concentration used. Both compounds significantly increased BBB permeability and altered protein and mRNA expression in BLECs. Influencing the BBB permeability in patients with brain metastases could increase the response rate to systemic therapy. Using HTS, we were able to accurately and quickly identify compounds that increase BBB permeability and show that using this type of screening method can be applied to endothelial paracellular permeability testing.